Narodziny parlamentaryzmu rosyjskiego w latach 1905-1906 w oczach Polaków - Sobczak, Jan (Acta Polono-Ruthenica, 2006)
The 100th anniversary of creation of the quazi parliament in the form of the State Duma as the Lower Chamber and in general reorganized State Council as the Upper Chamber takes place in 2006 and is of great interest not only historians but also of the specialists in study of literature, as they watch and research the social changes in the Russian state organization and can’t stand paying attention to the influence of this event on the political consciousness of the Russians of the first decade of the XXth century which was consolidated in a lot of works, also works of literature.The subject of the article is to show the attitude to that event of the Polish society, especially of the Poles from the Polish Kingdom, which was under the Russian reign in those times. The author represents this attitude through the utterances of the most influential people of the Polish public opinion, such as: Bolesław Prus, Jozef Piłsudski, Wladysław Studnicki, Tadeusz Grużewski, Hipolit Korwin-Milewski, Konstanty Skirmunt and gen. Jan Jacyna, also the utterances of the leading figures of ND, PPS and the editors of the popular „Kurier Warszawski”.A conclusion, to which the author comes on the basis of this discourse, is the following: inPolish opinion, in the majority of cases the skepticism prevailed, which regarded the reformatory possibilities of the Duma and also the attitude to the new system in Russia, which replaced the former autocratic tsarist absolutism in 1906, as a system, which, despite all its limitations, nevertheless was constitutional, and of Russia itself, as a monarchy, already representative.